Secondary Plastic Closure of Gastroschisis Is Associated with a Lower Incidence of Mechanical Ventilation - Dariel, Anne; Poocharoen, Wannisa; de Silva, Nicole; Pleasants, Hazel; Gerstle, Justin Ted (European Journal of Pediatric Surgery, 2015)
Introduction Nonsurgical closure after primary silo placement, secondary plastic closure (SPC), has been used as an alternative to secondary surgical closure (SSC) in gastroschisis. The benefits described were closure without formal surgical procedure, cosmetic aspect, and minimization of intra-abdominal pressures. This study compared requirements for mechanical ventilation and general anesthesia, nutritional care, and outcomes between SPC and SSC.Patients and Methods We included patients with primary staged-silo reduction with a 1-year minimum follow-up. SPC was performed at bedside with sedation using a nonadherent dressing. SSC was performed in operating room under general anesthesia using standard surgical techniques.Results This retrospective study included 64 patients, 23 SPC and 41 SSC. The characteristics of the two groups were comparable. Mechanical ventilation was used for 15 SPC and 41 SSC (p = 0.0001) with a comparable median duration (5.5 and 6.0 days, not significant [NS]). General anesthesia was required for 9 SPC and 41 SSC (p < 0.0001). Complications included one SPC and six SSC with necrotizing enterocolitis, zero SPC and four SSC with intestinal atresia, two SPC and four SSC with small bowel obstruction, zero SPC and one SSC with abdominal compartment syndrome resulting in a short bowel syndrome (NS). Median duration of parenteral nutrition (30 and 27 days), time to first feeds (14 and 14 days), time at or above minimal enteral feeding (22 and 17 days), time to full feeds (31 and 28 days), length of stay (LOS) in neonatal intensive care unit (24 and 23.5 days) and overall hospital LOS (37 and 36 days) were not statistically different between SPC and SSC patients without complications, respectively. These data were comparable for SPC and SSC patients with complications. Five SPC and six SSC developed an umbilical hernia (NS); two patients in each group required a surgical repair (NS).Conclusion Plastic closure of gastroschisis after primary silo reduction is simple, safe, reproducible, and associated with a significant lower incidence of mechanical ventilation. Nutritional management and length of hospital stay were similar to conventional surgical closure for patients. Plastic closure allows nonoperative management without general anesthesia at patient's bedside, in comparison with surgical closure that must be performed under general anesthesia in the operating room. Plastic closure does not appear to be associated with more umbilical hernias in this retrospective study.
Keywords: gastroschisis; secondary plastic closure; nonoperative management